Adsorption of Fecal Coliforms, Escherichia Coli in different soils in Sarawak - Ling, Teck Yee; Goh, Soon Hian; Kasing, Apun (Malaysian Journal of Soil Science, 2003)
In this study, fecal bacterial adsorption in three different soils (clay loam, silt loam, sandy loam) was investigated. A wild strain of &cherichia coli (E. colO isolated from animal wastewater was used in the study. For adsorption kinetics study, adhesion of bacterial cells to soil particles was found to be immediate. Percent adsorption was found to be dependent on the initial concentration of E.coli. Results indicate that at low E. coli concentrations (below I ()3 cfulml), the percent adsorption was very much less in sandy loam than in silt loam and clay loam. However, as the bacterial concentration increased, all the soils tested displayed higher bacteria adsorption with maximum values of 99.9% for clay loam, 99.9% for silt loam and 99.7% for sandy loam. Soil with higher clay content (35.2 % and lower pH (PH 4.5» had significantly higher capacity for adsorbing E. coli. Furthermore, E. coli concentration of I ()6 cfulml in suspension was found to decrease by 2 orders of magnitude in all the three soils. Therefore, land treatment of wastewater from animal farm lagoons should be considered to reduce microbial contamination of rivers.